Numerical investigation of the combined effects of a dimpled tube and Al2O3-CuO/water hybrid nanofluid on convective heat transfer - Oflaz, Fatma (Springer, 2026)
Enhancing heat transfer performance while maintaining acceptable pressure losses remains a critical challenge in the design of compact heat exchangers. In this context, surface modification techniques combined with advanced working fluids have attracted increasing attention as effective passive enhancement methods. This study numerically investigates the thermo-hydraulic performance of dimpled tube heat exchangers employing an Al2O3-CuO/water hybrid nanofluid, with the aim of identifying an optimal dimple configuration that maximizes heat transfer enhancement while minimizing flow resistance. The simulations are performed in ANSYS Fluent 2022 R2 using the RNG k-epsilon turbulence model under a constant heat flux of 25.5 kW m-2. Two dimpled tube configurations Model 1 with three dimples and Model 2 with six dimples were analyzed over a Reynolds number range of 5000-15,000. Based on previous studies, the dimple diameter and pitch were fixed at 3 mm and 10 mm, respectively, corresponding to geometries reported to yield favorable thermo-hydraulic performance. The hybrid nanofluid was modeled at a volume fraction of 1%. The results demonstrate that the synergistic interaction between dimpled geometry and hybrid nanoparticles significantly enhance convective heat transfer by promoting flow mixing and thinning the thermal boundary layer. Compared with a smooth tube, Model 2a achieved a 35-56% increase in the Nusselt number and a 22-34% increase in the friction factor, resulting in the highest performance evaluation criterion (PEC = 1.68), corresponding to a 68% improvement in overall thermo-hydraulic efficiency. Numerical predictions showed excellent agreement with experimental data from the literature, with maximum deviations of 5.32% for the Nusselt number and 9.86% for the friction factor. Overall, this study provides new quantitative insights into the combined role of dimpled tube and Al2O3-CuO/water hybrid nanofluids as a promising passive technique for enhancing heat exchanger performance, offering valuable guidance for the design of high efficiency thermal systems.
Keywords: Hybrid nanofuids; Dimple tube; Heat transfer enhancement; Thermal and hydraulic performance